Social effect of “cancel culture” on the digital environment: the case of generations Y and Z - L. Yu. Shuraeva; A. G. Korinets (Вестник университета)
“Cancel culture” is a significant phenomenon of modern digital communication, which has not been sufficiently studied due to its relative novelty. In this article operationalisation of the term “cancel culture” is carried out, and results of an empirical study conducted by means of a questionnaire, an expert poll and the theoretical analysis method were presented. The goal of the study was to assess social effects of the phenomenon using the example of generations Y and Z. To achieve this goal, elements of the external world that likely served as ideological origins of the phenomenon; its social purpose, value and establishment in the Internet environment; aspects of online communication that form “cancel culture”; as well as specific characteristics of groups that use it as an instrument of social control were studied. The conducted study supports the suggested hypothesis that “cancel culture” is a dysfunctional social regulation mechanism that is being formed for the following reasons: users’ pathological self-righteousness, tendency to jump to superficial conclusions, and inadequate and explicit aggression often manifesting itself as stigmatisation and bullying. Coupled with a binary perception of human behaviour, these factors cause the main problem of the “cancel culture” phenomenon – the imbalance of stimuli.